A new species of sponge crab of the genus Epigodromia McLay 1993 (Crustacea: Brachyura: Dromiidae) from the southeastern Arabian Sea, with notes on the Zoogeography - Prema, Mani; Cubelio, Sherine Sonia (Zootaxa, 2024)
A new dromiid crab, Epigodromia mclayi sp. nov., is described from the southeastern Arabian Sea and southwestern Bay of Bengal, India, based on 2 males collected onboard FORV Sagar Sampada cruises 392 and 236, respectively at depths of 107–113 m. Epigodromia mclayi sp. nov., resembles E. areolata (Ihle, 1913) from Indonesia and Australia but can be easily distinguished by the conspicuously rounded carapace with well-defined regions and areolate ornamentation, anterolateral margin with two lobes, each adorned with small 5–9 distinct teeth, relatively more inflated branchial region, presence of a large conical tooth behind the posterior branchial granular node, large rounded granular chelipeds, not strongly dimorphic, more tubular ambulatory legs with nodules on meri and propodi, dactyli with 5–7 small spines, and strongly reduced last pair of legs with propodi bearing three similar sized spines on the anterior margin and a distal spine on the posterior margin opposed to deeply curved dactylus. This is the second new species of Epigodromia McLay, 1993 discovered in Indian waters, it raises the species number 11.